THE IMPORTANCE OF USING VARIOUS METHODS DURING THE LESSON - Muxtorov Jo’rabek; Orzikulova Mavsuma (TADQIQOTLAR.UZ, 2024)
Abstract: This article gives general information about teaching methods, their types and differences. The posetive and negative sides of utilizing methods during the lesson. Traditional and modern methods. Choosing the appropriate method according to level and age of the students.